2008
DOI: 10.1111/j.1468-1331.2007.02041.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety amongst multiple sclerosis patients

Abstract: The aim of this study was to investigate the prevalence of symptoms of depression and anxiety amongst multiple sclerosis (MS) patients, and the associations with demographic and clinical characteristics. The current treatment for depression and anxiety was also evaluated amongst the MS patients. A total of 140 MS patients from Eastern Norway underwent neuropsychiatric and clinical examinations, with registration of symptoms of depression and anxiety (Hopkins Symptom Checklist-25), as well as information about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

34
170
6
19

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(229 citation statements)
references
References 36 publications
34
170
6
19
Order By: Relevance
“…The present study shows that persons with MS report symptoms of anxiety (20.2%) in a statistically significantly higher proportion than that in the normal population; these results are in line with other publications, for instance: Beiske, 19.3% [15]; Korostil, 18.6% [16]; Kehler, 25.0% [17]; and Dahl, 30.2% [18]. However, the prevalence of anxiety and its relation to socio-demographic and clinical characteristics of the MS patient population is much less thoroughly investigated than prevalence of depression in the general population and needs much more attention from scientists [19].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The present study shows that persons with MS report symptoms of anxiety (20.2%) in a statistically significantly higher proportion than that in the normal population; these results are in line with other publications, for instance: Beiske, 19.3% [15]; Korostil, 18.6% [16]; Kehler, 25.0% [17]; and Dahl, 30.2% [18]. However, the prevalence of anxiety and its relation to socio-demographic and clinical characteristics of the MS patient population is much less thoroughly investigated than prevalence of depression in the general population and needs much more attention from scientists [19].…”
Section: Discussionsupporting
confidence: 94%
“…After the multiple regression analysis, however, lower disability lost significance, but fatigue, pain and younger age at onset remained significantly associated with anxiety. Thus, our results agree with published figures and corroborate previous studies showing a high occurrence of anxiety symptoms in persons with MS [25]. The bio-psycho-social model of psychiatric disorders reminds us that not only biological and psychological factors, but also social factors, can play an important role in disease presentation,.…”
Section: Discussionsupporting
confidence: 93%
“…Conducting t-tests across the whole sample revealed that males were significantly more depressed and anxious than females, and had significantly lower life satisfaction. Intriguingly, these findings are generally inconsistent with the literature, which tends to show that females (regardless of whether or not they have multiple sclerosis) are more likely to experience mental health problems such as depression and anxiety [4,5].…”
contrasting
confidence: 74%
“…En este aspecto es preciso puntualizar que el instrumento usado por nosotros en la investigación de síntomas depresivos (cuestionario de Hamilton) no es el que predomina en la mayoría de las publicaciones sobre el tema en que se señala mayoritariamente el uso del inventario de Beck y la escala hospitalaria de depresión [30][31][32][33] . No obstante ello, nos pareció útil su uso debido a que constituye un instrumento aplicable a población ambulatoria consistente en una evaluación externa de los síntomas, que permite observar la evolutividad del cuadro y que brinda al entrevistador la posibilidad de distinguir las quejas somáticas debidas a un cuadro depresivo y las originadas por una afección médica.…”
Section: Discussionunclassified